2021
DOI: 10.2139/ssrn.3832481
|View full text |Cite
|
Sign up to set email alerts
|

Distressed Acquisitions: Evidence from European Emerging Markets

Abstract: We analyze factors behind 23,213 distressed acquisitions in European emerging markets from 2007-2019. Besides the impact of financial ratios, legal form, ownership structure, firm size, and age, we emphasize the role of institutions and channels of their propagation. We show that the quality and enforcement of insolvency laws are linked with the lower probability of distressed acquisitions, followed by corruption control and progress in banking reforms. The impact of institutions is larger in lessadvanced coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 66 publications
4
11
0
Order By: Relevance
“…Consistent with the arguments above, Iwasaki et al (2021) demonstrated that the quality and enforcement of insolvency laws are negatively associated with the probability of distressed acquisitions in European emerging markets, including Russia. In other words, they found that national-level institutional quality can effectively explain the differences in the frequency of distressed acquisitions across Eastern Europe.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…Consistent with the arguments above, Iwasaki et al (2021) demonstrated that the quality and enforcement of insolvency laws are negatively associated with the probability of distressed acquisitions in European emerging markets, including Russia. In other words, they found that national-level institutional quality can effectively explain the differences in the frequency of distressed acquisitions across Eastern Europe.…”
Section: Introductionsupporting
confidence: 71%
“…Therefore, in order to fully elucidate the determinants of distressed acquisitions in a country, the perspective of empirical analysis should be directed not only to national-level factors but also to those in regions. In this paper, we expand on the findings of Iwasaki et al (2021) by addressing this issue.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations